2023
DOI: 10.32649/ajas.2023.179725
|View full text |Cite
|
Sign up to set email alerts
|

Future Trends for Green Environmental Applications of Nanotechnology: A Review

G. Sh. Al-Obaidy,
M. F. Abdulrahman,
B. Sh. J. Alobaidy

Abstract: Review ArticleProviding a clean and safe environment is one of the great challenges facing humanity. As a result of various human activities over thousands of years in the field of agriculture, industry, housing, burning fuel and elimination of forests and agricultural areas, the environment has been greatly destroyed, and water, air and soil are polluted, and this has resulted in a several risks and problems that It began threatening humanity, perhaps the most important of which is the spread of diseases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(26 reference statements)
2
4
0
Order By: Relevance
“…The primary nitrogen source in the rumen is NH3-N, and its decrease from the standard range leads to a decrease in microbial protein production within the normal range 19,29 . Similar results reported that NH3-N concentrations were not affected by increasing levels of sage essential oils 15,16 . Contrary to our results, 3 reported a quadratic increase in NH3-N concentrations with increasing levels of sage oil in an in vitro study using rumen fluid from rams, regarding significant increases in TVFA concentrations in lambs fed low-level (SLP5) and medium-level (SLP10).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The primary nitrogen source in the rumen is NH3-N, and its decrease from the standard range leads to a decrease in microbial protein production within the normal range 19,29 . Similar results reported that NH3-N concentrations were not affected by increasing levels of sage essential oils 15,16 . Contrary to our results, 3 reported a quadratic increase in NH3-N concentrations with increasing levels of sage oil in an in vitro study using rumen fluid from rams, regarding significant increases in TVFA concentrations in lambs fed low-level (SLP5) and medium-level (SLP10).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding rumen fermentation variables, with no significant changes in ruminal pH with feeding sage leaves, the values were within the reference range for optimum microbial function 39 . Several in vitro studies reported 2,16 that increasing levels of sage essential oils do not affect ruminal pH. A similar observation was reported by 27, where no significant differences were observed in rumen pH when 0.2 g rosemary leaves /kg live body weight/ day were added to the diet of Barki lambs.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Thus, the potential future directions and trends of nanotechnology [ [195] , [196] , [197] , [198] , [199] , [200] , [201] , [202] , [203] , [204] ] about the 17 Sustainable Development Goals (SDGs) are extensive and varied and, based on all the above, can be summarized in different domains to be further investigated. Healthcare (SDG 3: Good Health and Well-being) [ 201 , 203 , 204 ]: Progress in developing nanoparticle-based targeted drug delivery systems to enhance the accuracy and effectiveness of illness treatment.…”
Section: Moving Forward and Future Directionsmentioning
confidence: 99%